Angel eyes - Lustbader, Eric 1946- (Fiction / Fawcett Crest ., 1993)
Unknown to one another, three brilliant determined women in Tokyo, Washington, and Moscow will ignite events that not only decide the fates of drug runners and Japanese Yakuza members, intelligence agents and arms brokers, but that could also change the face of the world map. They are all actors in a devious and deadly drama, where treachery awaits them at every turn, and enemies look like friends to the uninitiated....